Vascular complications after living donor renal transplantation at Santa Casa de Misericórdia São Paulo (101 cases) - Guidoni, Luiz Renato Montez; Korkes, Fernando; Fernandes, Roni De Carvalho; Perez, Marjo Cardenuto; Modesto, Augusto; Bosco, Álvaro; Krahembul, Gunther (Brazilian Journal of Transplantation, 2005)
Introduction: Kidney transplant subjects are more likely to present surgical complications than any other conventional surgery. Among these, vascular complications are the most outstanding. Objective: The aim of this study was to analyze vascular complications and its outcomes in kidney transplant recipients. Methods: A retrospective study consisting by 101 adults who underwent living donor renal transplantation at Sao Paulo Santa Casa between 1977 and 2005 (60 male; 41 female) was performed. Results: There were 8 cases of vascular complications (7.9%): six of them were arterial and two venousus complications. Six of those patients had lost their graft’s function or died and 2 had their kidney graft removed. There were two fatal complications (1.9%): one after arterial thrombosis, and the remaining after renal artery rupture. Conclusion: Vascular complications were uncommon events but led to severe complications with graft dysfunction in almost every case and even fatal outcomes.